Structural characterization of a homopolysaccharide with hypoglycemic activity from the roots of Pueraria lobata. Issue 8 (3rd August 2020) - Qian, Kai; Tan, Ting; Ouyang, Hui; Yang, Shi-Lin; Zhu, Wei-Feng; Liu, Rong-Hua; Wen, Quan; Feng, Yu-Lin
Abstract : A water-soluble neutral homopolysaccharide (PLP-1) was obtained from the roots of Pueraria lobata by DEAE cellulose and Sephadex G-200 gel chromatography purification. Abstract : A water-soluble neutral homopolysaccharide (PLP-1) was obtained from the roots of Pueraria lobata by DEAE cellulose and Sephadex G-200 gel chromatography purification. The average molecular weight of PLP-1 was 16.2 kDa. Monosaccharide composition analysis showed that PLP-1 was composed of glucose as a glucan. The structure of PLP-1 was characterized on the basis of extensive physical and chemical analysis, which indicated that the backbone of PLP-1 was mainly composed of →3)-α-d -Glc p (1→ and →4)-β-d -Glc p (1→ with a molar ratio of 7.0 : 1.0. Moreover, the hypoglycemic activity of PLP-1 was investigated by palmitic acid and high glucose induced insulin resistant HepG2 cells. The results elucidated that PLP-1 could decrease the glucose concentration by up-regulating the expression of PI3K and AKT, and down-regulating the expression of FoxO1, PCK2, and G6Pase in insulin resistant cells. Therefore, PLP-1 could serve as a dietary supplement to ameliorate insulin resistance for diabetic patients.